Design and Optimization of a New Efficient Furfural Production Technology via a Protic Ionic Liquid at “Quasi-Economic” Viability - Zhang,C; Ovejero-Pérez,A; Fennell,PS; Hallett,JP; Ghatta,AA (ACS Sustainable Chemistry & Engineering, 2026)
Abstract Furfural is a versatile bio-based aromatic building block with great potential for many applications. State-of-the-art processes rely on acid hydrolysis, with the main drawback being excessive wastewater generation with high biochemical oxygen demand. This implies environmental and regulatory challenges and requires extensive capital expenditure for large-scale adoption. Solvent-based approaches can improve process economics and reduce waste generation if criteria for recyclability and energy efficiency are met, thereby delivering a more cost-effective, sustainable process. Here, a protic ionic liquid-based approach is assessed using N,N-dimethylbutylammonium hydrogen sulfate ([DMBA][HSO4]), which previous studies have proven to be effective in biomass fractionation. This study shows that, under strict reaction control in terms of furfural separation, temperature regulation, and biomass feeding, competitive furfural yields can be achieved at a high biomass loading of 30 wt %, reducing energy demand and making this methodology competitive with traditional processes. This advance holds promise for reducing hazardous waste generation while improving the economic and environmental footprint of furfural manufacturing. This is the first study to combine high yield (∼75%), high biomass loading, solvent recyclability, and process economics for furfural production using a solvent-based approach.